Representation of Environmental Concepts Associated with Health Impacts in Computer Standardized Clinical Terminologies - Block, Lorraine J.; Lozada-Perezmitre, Erika; Cho, Hwayoung; Davies, Shauna; Lee, Jisan; Lokmic-Tomkins, Zerina; Peltonen, Laura-Maria; Pruinelli, Lisiane; Reid, Lisa; Song, Jiyoun; Topaz, Maxim; von Gerich, Hanna; Vyas, Pankaj (Yearbook of Medical Informatics, 2023)
Objective: To evaluate the representation of environmental concepts associated with health impacts in standardized clinical terminologies.Methods: This study used a descriptive approach with methods informed by a procedural framework for standardized clinical terminology mapping. The United Nations Global Indicator Framework for the Sustainable Development Goals and Targets was used as the source document for concept extraction. The target terminologies were the Systematized Nomenclature of Medicine Clinical Terms (SNOMED CT) and the International Classification for Nursing Practice (ICNP). Manual and automated mapping methods were utilized. The lists of candidate matches were reviewed and iterated until a final mapping match list was achieved.Results: A total of 119 concepts with 133 mapping matches were added to the final SNOMED CT list. Fifty-three (39.8%) were direct matches, 37 (27.8%) were narrower than matches, 35 (26.3%) were broader than matches, and 8 (6%) had no matches. A total of 26 concepts with 27 matches were added to the final ICNP list. Eight (29.6%) were direct matches, 4 (14.8%) were narrower than, 7 (25.9%) were broader than, and 8 (29.6%) were no matches.Conclusion: Following this evaluation, both strengths and gaps were identified. Gaps in terminology representation included concepts related to cost expenditures, affordability, community engagement, water, air and sanitation. The inclusion of these concepts is necessary to advance the clinical reporting of these environmental and sustainability indicators. As environmental concepts encoded in standardized terminologies expand, additional insights into data and health conditions, research, education, and policy-level decision-making will be identified.
Keywords: Nursing informatics; environmental health; standardized nursing terminology; systematized nomenclature of medicine; artificial intelligence